Agent-Based Mediation System to Facilitate Cooperation in Distributed Design (2009)
In this article we present the use of knowledge for a Mediation System, developed to give support to participants in mechanical-system-designer activities. To use a cooperative system sufficient assistance is needed to facilitate and coordinate actors’ activities. To accomplish this goal we introduce an artificial actor: Mediator.The Mediator forms part of the group of collaborative, with the specific role of facilitating the cooperative activity. This role of assistance, differentiate the Mediator from other actors. This one is endowed with specific skills of cooperation (communication; awareness, coordination, co-memorization), requiring some acquired knowledge, which allow them to give assistance to the human actors. We will define the types of knowledge defined for our proposed Mediation System. Then we will illustrate the use of memorized knowledge by the Mediator during an activity of technical functional analysis.